Evaluating spectral indices for water extraction: Limitations and contextual usage recommendations - Chuanwu Zhao; Haishuo Wei; Gudina Legese Feyisa; Thiaggo de Castro Tayer; Gelilan Ma; Hanyi Wu; Yaozhong Pan (International Journal of Applied Earth Observations and Geoinformation)
With the intensification of climate change and human activities, water resource shortages, floods, and water quality anomalies are becoming increasingly serious. It is urgent to ensure the effective realization of water resource management, flood monitoring, and water quality assessment through fine-scale monitoring of water body spatial distribution and dynamics. Currently, various technologies have been applied to water information monitoring, with remote sensing-based spectral index methods being widely used due to their simplicity, low cost, and large-scale observation capabilities. However, the wide variety of existing water spectral indices, each suited to different scenarios and objectives, makes it challenging for ordinary users to select the most appropriate index and determine its optimal usage (i.e., threshold settings). This study addresses these challenges by evaluating the performance and applicability of 15 widely used water detection indices, using Sentinel-2 imagery across 14 representative global regions. The results revealed that the performance of water indices varied across different scenarios. Common issues include misidentification in high-reflectance backgrounds (e.g., buildings and snow), low-reflectance backgrounds (e.g., shadows), and omission errors for water bodies with high chlorophyll content. On this basis, this study provides a recommended table for water body index selection in different scenarios and a recommended range table for index thresholds, and point out key directions for future development of water body indices. This study offers valuable guidance for the selection and use of water body indices in practical application, helping to enhance the accuracy and efficiency of fine-scale monitoring of water bodies.